GE_GERICHTE C/7335/2014 vom 6. Oktober 2017 - GE Cour de justice (2017)
DIVORCE LIQUIDATION DU RÉGIME MATRIMONIAL; PLUS-VALUE ; PRÉVOYANCE PROFESSIONNELLE ; OBLIGATION D'ENTRETIEN ; DÉPENS | CC.124.a; CC.125;